Analysis of Solar Radiation Availability for Deployment of Solar Photovoltaic (PV) Technology in a Tropical City - Olatona G. I; Adegoke C. W (International Journal of Applied Power Engineering (IJAPE), 2015)
The sunshine hours and solar radiation data for Ibadan (7° 30´ N, 3° 54´ E.), South West Nigeria in the last twenty years was analyzed, with a view to determining the abundance of solar energy available for deployment of solar photovoltaic (PV) technology applications. The measured solar radiation and actual sunshine hour data were obtained from International Institute of Tropical Agriculture (IITA), Ibadan. The data were analyzed using the statistical package of „origin 7‟ software. The maximum of 16.1MJm-2day-1 and minimum of 10.71MJm-2day-1 occurred in months of May and August respectively while the actual sunshine hour variation follows the same general trend but with the maximum of 6.99hrs in February and a minimum of 2.37hrs in August. At the current solar-to-electric conversion efficiency of 10%, the minimum solar radiation of 10.71MJm-2day-1 can supply a 1.0m2 solar panel a minimum of 44.6KWhr of Energy. Thus an abundance of solar energy has been established at Ibadan which in recent times has been witnessing incessant power outages from the national grid and thereby can contribute significantly to efforts in improving power supply mix. This implies that solar energy technology can thrive not only at Ibadan but in the whole of South West of Nigeria. Evidence of viability of PV technology in this area also abounds in the success of Solar Water Pumping stations recently installed by Government Agencies such as Ogun-Osun River Basin Development Authority (ORBDA) and the Millennium Development Goal (MDG) programmes in the area and environs.